Analysis of clinically-reported, memantine-induced cardiovascular adverse responses using the halothane-anesthetized dogs: Reverse translational study - Ryuichi Kambayashi; Ai Goto; Mihoko Hagiwara-Nagasawa; Hiroko Izumi-Nakaseko; Makoto Shinozaki; Shinichi Kawai; Akio Matsumoto; Yoshinori Takei; Atsushi Sugiyama (Elsevier, 2022)
Although NMDA receptor antagonist memantine is considered to be better tolerated than cholinesterase inhibitors on treating Alzheimer's disease, several types of cardiovascular adverse events have been associated with memantine treatment, including hypertension, myocardial infarction, severe bradycardia and QT-interval prolongation. In order to clarify how memantine induces these cardiovascular adverse events, we assessed its electropharmacological effects using the halothane-anesthetized dogs (n = 4). Memantine hydrochloride was intravenously administered in doses of 0.01, 0.1 and 1 mg/kg over 10 min, providing subtherapeutic, clinically-relevant and supratherapeutic concentrations, respectively. The low to high doses increased the mean blood pressure and left ventricular contraction and enhanced the atrioventricular nodal conduction, suggesting an increase of sympathicotonic output from the central nervous system similarly to donepezil, which might induce myocardial ischemia in patients with coronary artery disease. Meanwhile, the high dose suppressed the intra-atrial conduction and the low to high doses inhibited the intra-ventricular conduction, indicating potential to induce severe bradycardic adverse event by advanced cardiac conduction block in susceptible patients. Memantine alone did not induce repolarization delay, indicating lack of risk for inducing torsade de pointes. Thus, these in vivo experimental findings may provide basic information to better understand the clinically observed adverse events of memantine.